Book Review: Islamic Tourism; Management of Travel Destinations - Azzam, Hilmi Abdullah (Halal Tourism and Pilgrimage, 2024)
Islamic tourism is a rapidly growing sector in line with the increasing number of global Muslim tourists. The book Islamic Tourism: Management of Travel Destinations (Jamal, Raj & Griffin, 2019) presents a conceptual foundation, managerial approaches, and global case studies that illustrate the complexity of contemporary Islamic tourism practices. This article aims to summarize and analyze the contents of the book in a scholarly format, highlighting aspects of religiosity, culture, marketing, and destination management. The review indicates that Islamic tourism is not only oriented towards Shariah compliance but also towards creating spiritual, social, and ethical values that strengthen cross-cultural harmony. Key findings suggest the need for synergy between theology, technology, and destination governance in the development of sustainable Islamic tourism.